Per il Dante di Fernando Bandini - Massimo Natale (Parole Rubate, 2018)
Dante’s influence permeates Fernando Bandini’s poetry from the Sixties to his 2010 Quattordici poesie. This article offers an overview of Bandini’s Dantism through a selection of representative examples, including re-figurations of Dantesque situations, explicit intertextual tesserae or rewritings of wider scenes. Bandini’s relationship with Dante is not a ‘struggle with his literary father’, but rather the unlimited re-use of a maternally welcoming and freely citable Commedia.